2015
DOI: 10.15255/cabeq.2014.2022
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Inhibition Growth Kinetics for Cutinase Producing Pseudomonas cepacia Using Tomato-peel Extracted Cutin

Abstract: Using tomato-peel extracted cutin, an economically viable substrate, cutinase production by Pseudomonas cepacia was studied at different initial substrate concentrations (2-20 g L -1 ). The highest volumetric enzyme activity was observed at 10 g L -1 of cutin, which was inhibited at further higher concentrations. Various 3-, 4-and 5-parametric Monod-variant models were chosen to analyze the inhibition kinetics. The model parameters as well as goodness of fit were estimated using non-linear regression analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…The consumption of substrate plays an important role in both the growth of the cells and product formation, therefore the optimum concentration of substrate aids in the higher productivity of the desired product. In addition, the further application of a mathematical model helps in predicting the effect of environmental perturbation on the process and it provides information that can help maxime the objective function . Kinetic models are improved with an increase in complexity, therefore the Akaike information criterion (AIC) and the extra sum of squares F‐test are used to predict more consistent models from the experimental data …”
Section: Introductionmentioning
confidence: 99%
“…The consumption of substrate plays an important role in both the growth of the cells and product formation, therefore the optimum concentration of substrate aids in the higher productivity of the desired product. In addition, the further application of a mathematical model helps in predicting the effect of environmental perturbation on the process and it provides information that can help maxime the objective function . Kinetic models are improved with an increase in complexity, therefore the Akaike information criterion (AIC) and the extra sum of squares F‐test are used to predict more consistent models from the experimental data …”
Section: Introductionmentioning
confidence: 99%
“…Agarry and Solomon in 2008 studied the degradation of phenol by the fluorescence of Pseudomonas and observed that the experimental data of μ max corresponded well to the Haldane model. Dutta et al in 2015 by studying the production of cutinase by Pseudomonas cepacia did not conclude on the ideal model. Tazda et al 2013 found that the Yano and Andrews model best showed μ max when biodegradation of malathion.…”
Section: Resultsmentioning
confidence: 98%
“…These curves have a bell-like appearance and have two phases. A phase where the specific growth rates and maximal enzymatic activity increase with the formate concentration (1.59–3.17 mM) and a phase of decline of the specific growth rate and maximum enzymatic activity from 4.76 mM (Dutta et al 2015; Agarry et al 2010; Dey and Mukherjee 2010) proposed that this bell-like appearance at high substrate concentrations reveals inhibition by the substrate.
Fig. 6Influence of the initial ammonium concentration on the maximum enzymatic activity for Yarrowia lipolytica and Pichia guilliermondii strains
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the capability of the used models for simulating VFCW outflow concentrations of NH4 + and (NO2 -+NO3 -) was assessed by drawing the predicted concentrations as a function of observed VFCW outflow concentrations. The precision of the estimated parameters was assessed by the sensitivity analysis used by [39]. It comprised the effect of each estimate on the coefficient of determination, with only one estimate varied at a time, and a -50 to 50% variation range.…”
Section: Model Calibration and Simulationmentioning
confidence: 99%